Investigation and solution of bus bunching problem - Tan, Chun Howe (2014)
Buses of the same service route leave the interchange at the scheduled timings to maintain the required headway (in minutes) between buses. This headway differs for peak and non-peak hours. The public transport system this study will look into are both the public bus operator in Singapore, namely Singapore Bus Service (SBS) and Singapore Mass Rapid Transit (SMRT).